Masculinity and School Violence: Addressing the Role of Male Gender Socialization - Stoltz, Jo-Anne (Canadian Journal of Counselling and Psychotherapy, 2007)
The author argues for school-based violence prevention programming that addresses the unique predicament faced by male youth when they are asked to adopt attitudes and behaviours that may contradict traditional socialized notions of masculinity. Studies based on the Gender Role Conflict Scale (GRCS) and the Masculine Gender Role Stress Scale (MRGSS) are reviewed. The article also reviews recent research findings suggesting that boys respond differently to violence prevention programming in schools compared to girls. Tentative suggestions are made for violence prevention programming components that address the specific identity needs of male youth.